2020
DOI: 10.1007/s00468-020-02004-8
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry differs between male and female Juniperus communis L. independently of nutritional availability

Abstract: Key message Juniperus communis males are better adapted than females to changing, seasonal environmental conditions due to their higher photosynthetic capacity and the higher concentration of photosynthetic pigments in their needles. Males cope with ROS more efficiently than females having greater carotenoids concentration in needles. Abstract In dioecious woody plants, females often exhibit greater reproductive effort than male plants and as a res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 104 publications
1
12
0
Order By: Relevance
“…Low concentrations of nitrogen can influence growth in female plants due to lower photosynthetic capacity [23]. In the current study, the lower levels of nitrogen detected in needles of female plants of J. communis may be connected to the lower photosynthetic efficiency of females detected in a previous study [32]. It has been previously suggested that male individuals of J. thurifera use available nutrients to increase gas exchange capacity, while females exhibit a long-term strategy and increase N storage, saving N-reserves for reproduction [53].…”
Section: Carbon Nitrogen C:n Ratio and Other Elementssupporting
confidence: 56%
See 2 more Smart Citations
“…Low concentrations of nitrogen can influence growth in female plants due to lower photosynthetic capacity [23]. In the current study, the lower levels of nitrogen detected in needles of female plants of J. communis may be connected to the lower photosynthetic efficiency of females detected in a previous study [32]. It has been previously suggested that male individuals of J. thurifera use available nutrients to increase gas exchange capacity, while females exhibit a long-term strategy and increase N storage, saving N-reserves for reproduction [53].…”
Section: Carbon Nitrogen C:n Ratio and Other Elementssupporting
confidence: 56%
“…Notably, the highest air temperatures also occurred at this time, which may have affected starch accumulation as elevated temperature (more than 25 • C) can inhibit starch synthesis [48]. Additionally, our previous study shows that the high temperatures can also have a differential impact on leaf mass area (LMA) values in male and female plants; with females exhibiting a significantly higher LMA during the hottest month of the two years of the study (females 156.78 ± 3.13 and males 147.35 ± 3.23, p = 0.0465) [32]. The thicker lamina present in leaves of female plants, relative to male plants, can better protect cells against a sharp rise in temperature [49].…”
Section: Carbohydratesmentioning
confidence: 88%
See 1 more Smart Citation
“…Although no studies have specifically reported the chlorophyll content of J. communis L. species, Rabska and colleagues [ 56 ] analyzed their total levels in fertilized and nonfertilized in both genders of this plant in autumn and winter (species not specified). The obtained data revealed nonfertilized plants had a lower concentration of total chlorophyll content than the fertilized ones (mean values of 5.0 versus (vs.) 7.4 mg/g in autumn and 3.6 vs. 4.8 mg/g in winter, respectively), and also lower amounts of total carotenoids (mean values of 0.64 and 0.95 mg/g for female and male, respectively, in autumn, and scores of 0.87 against 1.2 mg/g in winter).…”
Section: Phytochemical Composition Of Juniperus Communis ...mentioning
confidence: 99%
“…This suggests that, although in a rich environment, female plants invest more into production of numerous flowers, while the efficiency of seed development and seed production is related to factors other than just nutritional availability and pollen availability [ 47 ]. Moreover, our earlier studies showed that fertilised female plants of both species are characterised by higher photosynthetic activity [ 38 , 48 ] and higher biomass [ 39 ] than their non-fertilised counterparts. These observations indicate that the allocation of plant resources to seed production is a reasonable/controlled investment of resource allocation; thus, in a non-fertilised environment, when the plant has already invested part of the available resource for female reproductive structure development, the necessary resources were provided by the plant (at the cost of vegetative growth or resource allocation) to ensure development of seeds [ 47 ].…”
Section: Discussionmentioning
confidence: 99%